Analisis Putusan KPPU yang Melampaui Kewenangan Berdasarkan UU Larangan Monopoli dan Persaingan Usaha - Benedictus Rumagit, Rian (Fakultas Hukum, Universitas Islam Balitar, 2024)
This study highlights the importance of consistency in the application of KPPU's authority in accordance with the Anti-Monopoly and Unfair Business Competition Law. There is a research gap regarding the alignment of KPPU's sanctioning authority, particularly in Decision Number 17/KPPU-I/2018. The study aims to analyze the sanctioning authority of KPPU and its compliance with Law Number 5 of 1999. A normative juridical method is used to examine the decision and relevant laws, focusing on the limits of KPPU's authority. The key findings indicate that KPPU's Decision Number 17/KPPU-I/2018 exceeds the authority stipulated by the law, especially in imposing administrative measures on business actors violating Article 22. The implication is that KPPU must adhere to its authorized limits to ensure the effectiveness of competition law enforcement in Indonesia.